The Effect Of Incentives And Work Environment On Employee Satisfaction Of Palembang City's Regency Service - Febriadi, Yendi; Yustini, Tien; Alie, Marzuki (UNIVED Press, 2026)
Employee satisfaction is a crucial element that determines the overall performance, productivity, and service quality of any organization, particularly in the public sector. In government institutions such as the Regency Service Office in Palembang City, employee satisfaction plays a vital role in ensuring that public services are delivered efficiently, responsively, and with a high standard of professionalism. the context of the Palembang City Regency Service, which is tasked with providing direct services to the public, the satisfaction of its employees is essential for ensuring consistent and high-quality service delivery. However, various challenges such as inadequate incentive structures and suboptimal work conditions may hinder employee performance and motivation. Therefore, it becomes imperative to investigate how incentives and the work environment impact employee satisfaction in this specific governmental context. The findings of this research are expected to provide practical implications for policymakers and government administrators. Specifically, the results will offer insights into how incentive systems and improvements in the work environment can be used to increase job satisfaction among civil servants, thereby supporting better governance and public service delivery.